Chromosome Microarray. Issue 5 (September 2016) - Anderson, Sharon
Abstract : Abstract: Over the last half century, knowledge about genetics, genetic testing, and its complexity has flourished. Completion of the Human Genome Project provided a foundation upon which the accuracy of genetics, genomics, and integration of bioinformatics knowledge and testing has grown exponentially. What is lagging, however, are efforts to reach and engage nurses about this rapidly changing field. The purpose of this article is to familiarize nurses with several frequently ordered genetic tests including chromosomes and fluorescence in situ hybridization followed by a comprehensive review of chromosome microarray. It shares the complexity of microarray including how testing is performed and results analyzed. A case report demonstrates how this technology is applied in clinical practice and reveals benefits and limitations of this scientific and bioinformatics genetic technology. Clinical implications for maternal–child nurses across practice levels are discussed. Abstract : A comprehensive review of chromosome microarray is presented including how testing is performed and results are analyzed. A case report highlights how the technology is applied in clinical practice and the benefits and limitations of scientific and bioinformatics genetic technology. This information is valuable for maternal child nurses in all practice settings.